Utilizing Social Media in Arabic Language Learning: Its Impact on Writing Skill, Vocabulary Acquisition, and Student Motivation - Tauhid; Muhammad Yusuf Salam; Rahmad Hidayat; Irmasani Daulay; Indra Saputra (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2025)
The rapid advancement of technology has significantly influenced various aspects of education, including language learning. Among the emerging trends in modern education, the use of social media as a language learning tool has become increasingly prominent. However, limited research has examined its direct impact on students’ writing skills, vocabulary acquisition, and learning motivation in Arabic. This study aims to investigate and analyze the influence of social media use on writing skills, vocabulary development, and the motivation of Arabic language learners. A mixed-methods approach was employed, combining quantitative surveys and qualitative analysis of free writing samples from 40 students in the Arabic Language Education program at STAIN Mandailing Natal, selected through purposive sampling. The findings indicate a significant improvement in writing abilities, particularly in sentence structure, vocabulary choice, and grammatical accuracy, following Arabic language learning through social media. This improvement is attributed to the contextual and communicative learning environment that social media platforms provide, which supports the development of students’ writing abilities. Moreover, students demonstrated notable vocabulary acquisition through active engagement on social media platforms such as TikTok, Instagram, and Facebook. Their motivation to learn Arabic also increased, as evidenced by a stronger desire to continue their language studies. In conclusion, the integration of social media into language learning can enhance students’ writing performance, broaden vocabulary mastery, and boost motivation. The study recommends further exploration of technology-based language learning methods to optimize Arabic education at the tertiary level. التطور السريع في التكنولوجيا يؤثّر بشكل كبير على مختلف جوانب التعليم، بما في ذلك تعلم اللغات. ومن بين الاتجاهات الناشئة في التعليم الحديث، أصبح استخدام وسائل التواصل الاجتماعي كأداة تعليمية للغة أكثر بروزًا. ومع ذلك، لا تزال الدراسات التي تتناول التأثير المباشر لهذا الاستخدام على مهارة الكتابة، واكتساب المفردات، ودافعية الطلاب في تعلم اللغة العربية محدودة. يهدف هذا البحث إلى دراسة تأثير استخدام وسائل التواصل الاجتماعي على مهارة الكتابة، وتطوير المفردات، ودافعية طلاب اللغة العربية. استخدم البحث منهجية مختلطة، تجمع بين الاستبيانات الكمية والتحليل النوعي لعينات الكتابة الحرة من أربعين طالبًا في برنامج تعليم اللغة العربية في جامعة STAIN Mandailing Natal ، والذين تم اختيارهم باستخدام أسلوب العَيِّنَة القَصْدِيّة. أظهرت النتائج تحسنًا ملحوظًا في مهارة الكتابة، خاصة في بناء الجمل، واختيار المفردات، ودقة القواعد، بعد المشاركة في تعلم اللغة العربية باستخدام وسائل التواصل الاجتماعي. ويُعزى ذلك إلى أن وسائل التواصل الاجتماعي توفّر بيئة تعليمية سياقية وتواصلية تُسهم في تطوير مهارات الكتابة لدى الطلاب. كما اكتسب الطلاب مفردات جديدة بشكل ملحوظ من خلال تفاعلهم على منصات التواصل مثل تيك توك، وإنستغرام، وفيسبوك. وزادت دافعيتهم نحو تعلم اللغة العربية، مما يدل على رغبتهم المتزايدة في مواصلة دراسة اللغة. وخلصت الدراسة إلى أن دمج وسائل التواصل الاجتماعي في تعليم اللغة يمكن أن يعزز مهارات الكتابة، ويوسّع المفردات، ويزيد من دافعية الطلاب. ويوصي البحث بمزيد من الاستكشاف لطرق التعلم القائمة على التكنولوجيا لتعزيز تعليم اللغة العربية في التعليم العالي.